2020
DOI: 10.1038/s41598-020-74445-7
|View full text |Cite
|
Sign up to set email alerts
|

B-box transcription factor 28 regulates flowering by interacting with constans

Abstract: B-box transcription factors (BBXs) are important regulators of flowering, photomorphogenesis, shade-avoidance, abiotic and biotic stresses and plant hormonal pathways. In Arabidopsis, 32 BBX proteins have been identified and classified into five groups based on their structural domains. Little is known about the fifth group members (BBX26–BBX32) and the detailed molecular mechanisms relevant to their functions. Here we identified B-box transcription factor 28 (BBX28) that interacts with Constans (CO), a transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 61 publications
2
24
0
1
Order By: Relevance
“…A flowering regulation pathway consisting of AtCO-AtFT-AtSOC has been established in Arabidopsis [53,54]. Our results show a downregulation of those genes in the overexpression lines, which suggests that FaBBX28c1 may function as an upstream negative regulator of the pathway (Figure 13), which is similar to its homologs in Arabidopsis [6]. In addition, recent works from strawberry also confirm the pathway of FvCO-FvFT1-FvSOC1 in the control of flowering time [10,55].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…A flowering regulation pathway consisting of AtCO-AtFT-AtSOC has been established in Arabidopsis [53,54]. Our results show a downregulation of those genes in the overexpression lines, which suggests that FaBBX28c1 may function as an upstream negative regulator of the pathway (Figure 13), which is similar to its homologs in Arabidopsis [6]. In addition, recent works from strawberry also confirm the pathway of FvCO-FvFT1-FvSOC1 in the control of flowering time [10,55].…”
Section: Discussionsupporting
confidence: 75%
“…It is well understood that AtBBX19 plays dual roles in the regulation of flowering time in Arabidopsis and tolerance to drought stress in chrysanthemum [9,48]. However, the function of AtBBX28 remains contentious [6,7]. In the present study, the highest expression of FaBBX19 and FaBBX28 was also observed in the root tissue.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…The CaBBX11 and CaBBX19 were under-expressed in leaves but over-expressed in other organs. While ABBX28 , the homologous gene of CaBBX28 encodes an atypical B-box domain protein that negatively regulates photomorphogenic development by interfering with the binding of the transcription factor, HY5, to its target gene promoters ( Liu et al, 2020c ). In this study, GO enrichment analysis indicated that CaBBX s of pepper were widely expressed and enriched spanning across all the stages of fruit development, and their functions were closely related to the differences in their domains, structures, promoters, and evolutionary processes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some phyB photobodies may contain cryptochromes, which are blue light receptors (reviewed by van Buskirk et al, 2012). Apart from photoreceptors, the composition of the photobodies includes transcription factors, such as Constans (CO) and the B-box transcription factor 28 (BBX28), 10.3389/fpls.2022.984163 or the E3 ligase constitutively photomorphogenic 1 (COP1; Liu et al, 2014Liu et al, , 2020.…”
Section: Photobodiesmentioning
confidence: 99%